Kekerasan di Televisi: Perspektif Kultivasi - Yohana, Nova; Ahmadi, Dadi (Mediator, 2007)
Indonesians are categorized as Views Society, i.e. society who significantly spent most of their leisure times in front of the screen, instead of doing other activities, such as reading. Television, on the other hand, proved to be an effective media whose outreach and penetration potent were undefeatable compared with other media. This situation turns to be problematic, due to the low quality of television which contained violence materials. People naturally learn violence from television. Being overexposed to violence materials, people were getting used to solve their problems by means of violence, too.